2019
DOI: 10.1088/1361-665x/ab1143
|View full text |Cite
|
Sign up to set email alerts
|

Development of an SMA-based camber morphing UAV tail core design

Abstract: This paper presents a new design for the core of a lightweight tail section of an unmanned aerial vehicle (UAV) with camber-morphing horizontal and vertical stabilizers. The core of each stabilizer is composed of an aluminum spar, two active end ribs, and multiple inactive ribs. Each active end rib is composed of a solid leading compartment connected to a flexible corrugated trailing segment. Thermally activated shape memory alloy (SMA) wire actuators along the length of the corrugated segment are used to cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Morphing wings enable aircraft to optimize flight mode by changing wing shapes through active adjustment of wing shapes corresponding to external or internal flight conditions while flight [ 1 , 3 , 7 , 8 , 9 , 10 ]. Most works in morphing focus on the mechanisms concerning conventional mechanical design or Smart materials and their proof-of-concept stages and material/structure-based internal mechanisms, which are far from realization and test flight of morphing aircraft [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…Morphing wings enable aircraft to optimize flight mode by changing wing shapes through active adjustment of wing shapes corresponding to external or internal flight conditions while flight [ 1 , 3 , 7 , 8 , 9 , 10 ]. Most works in morphing focus on the mechanisms concerning conventional mechanical design or Smart materials and their proof-of-concept stages and material/structure-based internal mechanisms, which are far from realization and test flight of morphing aircraft [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the morphing wing research works focus on either the design and implementation of morphing concepts using selected materials and structures [4][5][6][7][8][9][10][11], or the analysis Most of the morphing wing research works focus on either the design and implementation of morphing concepts using selected materials and structures [4][5][6][7][8][9][10][11], or the analysis of the structural and aerodynamic performance of suggested morphing concepts and their mechanisms [12][13][14][15]. Researchers have developed camber morphing mechanisms using smart materials [16][17][18], corrugated structures [19], multi-unit rib structures [20], vertically slitted rib structures [21], truss elements and runners [22], pressure-actuated cellular structures [23,24], bio-inspired FishBAC structures [25], monolithic compliant mechanisms [26], or combined form [27] to introduce and validate their effectively working models and design implementation. Some morphing wing design implementations were even validated with an effectively flown test model [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Planform morphing includes resizing the span and chord lengths and modifying the sweep angle [4]. Out-of-plane morphing includes twisting, change in dihedral angle, camber-morphing, and span-wise bending [5][6][7]. Airfoil morphing includes reshaping the airfoil profile and thickness.…”
Section: Introductionmentioning
confidence: 99%
“…With the advancements in smart materials, like shape memory alloys (SMA) and piezoelectric materials, many researchers have been developing innovative methods of incorporating smart materials and compliant structures into morphing wings [5,12,[25][26][27]. Barrett [25] showed that twist-morphing can be induced with the use of bimorph piezoelectric actuators.…”
Section: Introductionmentioning
confidence: 99%